2016
DOI: 10.1186/s12884-016-1167-6
|View full text |Cite
|
Sign up to set email alerts
|

Provider adherence to first antenatal care guidelines and risk of pregnancy complications in public sector facilities: a Ghanaian cohort study

Abstract: BackgroundGuideline utilization aims at improvement in quality of care and better health outcomes. The objective of the current study was to determine the effect of provider complete adherence to the first antenatal care guidelines on the risk of maternal and neonatal complications in a low resource setting.MethodsWomen delivering in 11 health facilities in the Greater Accra region of Ghana were recruited into a cohort study. Their first antenatal visit records were reviewed to assess providers’ adherence to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 50 publications
(45 reference statements)
7
38
4
Order By: Relevance
“…The incidence of PIH and PPH is about 4.7% and 3.7% respectively in this study. This study is different from a Ghana study which is 5.3% and 2.1% respectively for PIH and PPH (3). The variation of these results might be because of the time of study and nature of the countries.…”
Section: Incidence Of Maternal and Neonatal Complicationcontrasting
confidence: 92%
See 2 more Smart Citations
“…The incidence of PIH and PPH is about 4.7% and 3.7% respectively in this study. This study is different from a Ghana study which is 5.3% and 2.1% respectively for PIH and PPH (3). The variation of these results might be because of the time of study and nature of the countries.…”
Section: Incidence Of Maternal and Neonatal Complicationcontrasting
confidence: 92%
“…Incidences of those two maternal complications among the exposed and non-exposed groups were 1.6:6.2 and 2.6:4.3% respectively. ( Table 3) In this study the overall antenatal complication was about 21% which is lower than the study conducted in Ghana where antenatal complication was 68.1% (3).This variation could be due to the programme and follow up implemented now in every country is strict and Ethiopia is one of the nations which follow this agendum. That might be the reason why antenatal complication is reduced.…”
Section: Incidence Of Maternal and Neonatal Complicationcontrasting
confidence: 51%
See 1 more Smart Citation
“…Several studies have reported the usefulness of treatment guidelines in general and for speciic diseases notably epidemics such as HIV and noncommunicable diseases [3][4][5][6]. In summary, treatment guidelines and algorithms for management of speciic diseases and conditions: Unfortunately, with regard to poisoning incidents, national treatment guidelines of several countries have shortcomings as guidance and algorithms on speciic poisoning agents are not presented there in [7].…”
Section: Importance Of Guidelines and Algorithms In Diagnosis And Manmentioning
confidence: 99%
“…Using guidelines during clinical practice has several bene ts for both the provider and end service users. These bene ts include improving client outcomes, ensuring uniformity of care, improving the process and structure of care, and helping providers to make clinical decisions (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%